Characterization of Materials and Artistic Techniques on Two 17th‐Century Neapolitan Wood Sculptures. (3rd November 2017) - Fico, D.; Faraco, M.; Pennetta, A.; Rizzo, D.; De Benedetto, G. E.
Abstract : Two sculptures of Gaetano Patalano, one of the most important Italian sculptors of the late 17th century, were analysed to study the stratigraphy, the organic and inorganic materials, and to distinguish the original layers from the repaintings. Samples taken from the Immacolata Concezione and from San Gaetano da Thiene (Santa Chiara church, Lecce, Italy) were studied by optical microscopy, μ‐Raman spectroscopy and Py‐GC–MS. Different binders and pigments were used for the preparatory layers on the different parts of the statues: the results demonstrate that Patalano mastered the various materials and techniques, and that his choices have allowed his carving ability to be emphasized.